2003
DOI: 10.1002/jgm.445
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ultrasound‐mediated gene transfection by membrane modification

Abstract: This enhancement could be useful for ultrasound-mediated gene therapy in the future since both treatments for membrane modification could be directly applied to the living body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 32 publications
(36 reference statements)
3
34
0
Order By: Relevance
“…However, this also influences the stiffness of the lipid microbubble shell [31], thereby changing the ultrasound-responsiveness and behavior of the microbubbles [32]. Moreover, cell membrane fluidity is affected by temperature and this may again alter the vulnerability of cells to sonoporation [33]. A lower temperature as well as ATP depletion may hinder pore repair, since this is an energy-dependent process [19].…”
Section: Dependence Of Uptake Route On Acoustic Pressure and Moleculementioning
confidence: 99%
“…However, this also influences the stiffness of the lipid microbubble shell [31], thereby changing the ultrasound-responsiveness and behavior of the microbubbles [32]. Moreover, cell membrane fluidity is affected by temperature and this may again alter the vulnerability of cells to sonoporation [33]. A lower temperature as well as ATP depletion may hinder pore repair, since this is an energy-dependent process [19].…”
Section: Dependence Of Uptake Route On Acoustic Pressure and Moleculementioning
confidence: 99%
“…Many studies have demonstrated that ultrasound (US) can delivery DNA, proteins, and other formulations of molecules of interest into viable cells [1][2][3][4][5][6][7][8]. It has been hypothesized that US energy, often amplified by microbubble activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compelling results obtained recently have stimulated great interest in the development of sonoporation applications with exciting possibilities [1][2][3][4][5][6][7][8]. However, progress in the field is hindered by a lack of mechanistic understanding of the sonoporation process and its outcome beyond demonstrations of initial feasibility [20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasound in therapy (6,7) and also in gene transfection (8)(9)(10)(11)(12) has been investigated both in vitro and in vivo. Poor transfection rates remain a problem, so combinations with other methods are being used to try to improve the outcomes.…”
mentioning
confidence: 99%